Microbial Composition Change and Heavy Metal Accumulation in Response to Organic Fertilization Reduction in Greenhouse Soil - Qin Qin; Jun Wang; Lijuan Sun; Shiyan Yang; Yafei Sun; Yong Xue (Microorganisms)
Increased application of organic fertilizer is an effective measure to improve greenhouse soil quality. However, prolonged and intensive application of organic manure has caused nutrient and certain heavy metal accumulation in greenhouse soil. Therefore, the optimal quantity of organic manure required to sustain soil fertility while mitigating the accumulation of heavy metals and other nutrients resulting from continuous application remains unclear. This study evaluated the impacts of sustained and reduced organic manure application on soil physicochemical properties, heavy metal contents, and microbial community through a 9-year greenhouse field experiment. Treatments included a control without any fertilizer (CK), conventional manure (M), and three reduced manure treatments (−25%M, −37.5%MNPK, and −50%MNPK). Compared to CK, either M treatment or manure reduction treatments either maintained or significantly elevated soil pH and soil organic matter, total nitrogen, total phosphorus, and available phosphorus. Notably, −37.5%MNPK exhibited further increases in the available nitrogen and potassium. The M treatment significantly increased in the total concentrations of cadmium, copper, lead, zinc, and the availability of chromium and zinc. However, reduced manure treatments showed no change or a significantly reduced in heavy metal availability. The −25%M and −37.5%MNPK treatments significantly improved bacterial diversity. Reducing organic manure altered microbial taxa abundance. The soil pH emerged as the primary driving factor for variation in the bacterial community structure, whereas available nitrogen, potassium, and lead were the key factors influencing fungal community structural changes. These results indicate that reducing excessive organic manure input is an effective strategy to control heavy metal accumulation, enhance soil fertility, and optimize microbial community structure.